Effects of travel on professional Rugby Union players - Lo, M. (Victoria University Melbourne, 2018)
Super Rugby is an international competition played in the southern hemisphere with participating teams required to undertake multiple travel during a season. This thesis investigated the direct and complex relationship between regular air travel and athletes` psycho-physiological response and performance. The first two studies investigated the impact of travel on team performance during the first 21 years of the competition (1996-2006). Study 1 showed the predominant role of the away-match disadvantage in determine match results following the longest flights and greatest time zones shifts, whilst the results from study 2 suggests that fatigue related to long-haul travel and the increased physical demand of the game negatively impacted team performance measured using Key Performance Indicators. Study 3 was a socio-physiological analysis of all travel related issues and solutions, as reported by travel managers from eight Super Rugby teams. The results show that psychological and emotional well-being may take primacy over physiological wellness as team culture and cohesion may be as important as biological interventions in controlling the negative effects of travel on players` performance and well-being. Studies 4 and 5 monitored players from four teams and investigated their individual response to long-haul trans-meridian travel, with a focus on sleep (study 4), wellness and performance (study 5). The results suggest that, although the effects of travel on individual performance appear to be limited, long-haul travel had a substantially negative impact on players` sleep and wellness. Further studies should investigate the potential impact of sleep disruptions and reduced wellness on players` general health and well-being. The findings of this thesis should be of interest to all coaches and supporting staff in sports that require international travel to compete.